ANÁLISIS DE RESIDUOS SÓLIDOS Y ALTERNATIVAS PARA MINIMIZAR SU EFECTO EN UMA ENSEÑANZA JOVEN DY UNIDA DY RIO DE JANEIRO ADULTOS - Antonio Carlos do Prado Ribeiro; Elizabeth dos Santos Rios (Universidade do Estado do Rio de Janeiro, 2015)
<!-- p { margin-bottom: 0.25cm; direction: ltr; line-height: 120%; text-align: left; widows: 2; orphans: 2; }p.western { font-size: 11pt; }p.cjk { font-size: 11pt; }p.ctl { font-size: 11pt; }a:link { color: rgb(0, 0, 255); }a.western:link { }a.cjk:link { }a.ctl:link { font-family: "Times New Roman"; } --> The unplanned growth of cities has caused problems for human society due to ignorance of the impacts that would be caused to the environment. The uncontrolled use of raw materials and energy undertakes various ecosystems and causes pollution on a global scale that can affect future generations and different ways of life. This study was conducted in an Educational Unit and young adults of high school and aimed to reinforce the importance of preserving the environment through the management and proper disposal of solid waste produced in high school. The school routine with respect to solid waste management was observed in a total of sixteen days, where the segregated waste were analyzed and weighed. Data were grouped in tables and graphs, contributing to the development of alternatives and activities in environmental education proposals, in order to minimize the effects of solid waste in the school environment and community.   DOI: http://dx.doi.org/10.12957/sustinere.2015.17329